Reinvigorating a Traditional Balinese House: Managing Tourist Facilities and Maintaining Architectural Traditions - Adhika, I Made; Putra, I Dewa Gede Agung Diasana (Universitas Ibn Khaldun Bogor, 2023)
Traditional Balinese houses in tourist areas are transforming, whereas, on the other hand, Balinese have tried to maintain the identity of the traditional houses to attract tourists. This transformation is a paradoxical phenomenon in which people have transformed their houses to gain economic benefits from tourism. The absence of an appropriate transformation model, which can be used as a guide for the community in utilizing houses in tourism economic activities, allows for the filtration of the tourism function into traditional spatial and cultural spaces. Therefore, this study is urgent to be carried out to maintain the potential of the house as a cultural tourist attraction while at the same time gaining economic benefits. To achieve this goal, a tiered method was developed starting from baseline data collection, an inventory of the texture and character of changes in traditional houses. A more in-depth exploration of traditional house changes using samples based on stratified random sampling and interviews will reveal and create traditional house change innovations. It is continued with the creation of design innovations in the traditional house transformation model. Finally, an analysis was carried out on creating design innovations to transform traditional houses into tourist facilities without abandoning the meaning and values of a traditional house.